(untitled) (Kairaranga, 2010)
This seven month trial was undertaken to determine if the Fonetik spelling system (Jackson, 1994) enabled students with and without spelling difficulties to enhance their regular spelling scores. A sample of 270 students aged between 8 and 13 years were involved. The students were based in 8 schools within an RTLB cluster. The Fonetik system was introduced to all the students within their regular classroom settings. The results indicate that Fonetik was successful in increasing regular spelling scores for students with spelling difficulties and that it can be successfully implemented in schools with guidance from RTLB. This matched the conclusions of the first trial conducted by Croft and Boyd with the support of NZCER (1993).